IMPLEMENTASI HIBAH KANTOR DIREKTORAT JENDRAL PERBENDAHARAAN (DJPB) MELALUI PEMANFAATAN BARANG MILIK NEGARA (BMN) BEKAS PAKAI - Siti Sarah Nasution; Asyari Hasan (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
The purpose of this research is to find out how the implementation of the role of BMN DJPB grants to the community economy. It is hoped that the grant from BMN DJPB can improve the standard of living of the Muslim community. The research methodology used in this research is qualitative descriptive using methods of study literature and policies / regulations related to research problems. While the analysis method used is SWOT analysis. The results showed the transfer of state-owned goods through the grant mechanism is still very little done. Out of a total of 34,283 units of state-owned goods that were abolished, the transfer by grant mechanism was only 1,454 units or 4% of goods were given from all goods. The implication of this study is that it produces maximum benefits for the people and for the economy to create prosperity. Thus, state-owned goods obtained using state budget funds must also produce maximum benefits for the people.